Malignant schwannoma of the sciatic nerve originating in a spinal plexiform neurofibroma associated with neurofibromatosis type 1 - Case report - Topsakal, C; Akdemir, I; Tiftikci, M; Ozercan, I; Aydin, Y (Japan Neurosurgical Soc, 2001)
A 26-year-old man with neurofibromatosis type 1 (NF1) presented with a giant malignant schwannoma of the sciatic nerve. The differential diagnosis of malignant peripheral nerve sheath tumor (MPNST) was based on clinical, radiological, and histological evidence. The tumor apparently originated in a spinal plexiform neurofibroma. The lesion was resected totally without neural damage to the sciatic nerve. However, the tumor recurred within 2 months. The patient died of unknown factors probably associated with the spinal involvement. MPNST associated with NF1 has a poor prognosis due to recurrence or metastasis despite complete macroscopic removal.
Keywords: neurilemmoma; neurofibroma; malignant peripheral nerve sheath tumor; malignant schwannoma; von Recklinghausen's disease